Emotional intelligence role in academic performance in smart and ordinary schools - Soghra Ebrahimi Ghavam, Ismail Sadipour,; Farrokhi, Noorali; Nahid Sameti, Hassan Assadzadeh, (Opción, 2019)
The main purpose of this study is to determine role of emotional intelligence in academic performance of students in smart and ordinary schools. The method applied in this study is correlation in kind of prediction. Statistical population consists of all high school students of Tehran. The results obtained from the study showed that the direct and indirect effect of emotional intelligence on academic performance of students is significant. As a conclusion, it could be mentioned that role of smart schools in underlying variables such as emotional intelligence and academic performance can clear and highlight role importance of smart schools